Ejercicios Psicomotrices Sugeridos Para Los Grados Iniciales De Básica Primaria (2003)
The present essay entitled, the beneficial psychomotriz exercises essential for children of first grade of primary school, began with the following question: which is the influence of a physical education program centred in the psychomotricity for children of first grade (ages between 5 to 8) of Adiela’s primary school located in the municipality of Armenia, Quindío? To the above question, a hypothesis was given: if a physical education program centred in the psychomotricity is applied with correct positions and movements to the children of first grade, the problems of laterality presented in the kids will be corrected. In that way, the wrong motricity or the lack of laterality guided the researcher to the development of a program of a psychomotriz education that had the intention to avoid or correct the deficiencies of laterality shown in a group of children between 5 to 8. The benefits offered by the program answered the expectations that the researcher had in mind.